The Effect of Effleurage Massage on the Scale of Back Pain in Pregnant Women in the Third Trimester at TPMB (Midwife Independent Practice) Ratna Dewi, Gunung Putri District, Bogor Regency, Indonesia - Ratna Dewi; Shanti Hekmawati (HM Publisher, 2023)
Effleurage is a massage technique commonly used in relaxation massage and therapeutic massage. This technique involves massaging the surface of the skin gently and repeatedly using the palms of the hands or fingers. Effleurage is usually used as part of an initial massage to prepare the client's body before deeper massage techniques are used. The gentle, rhythmic movements of effleurage help relax clients physically and mentally. This light, regular touch helps reduce muscle tension and improves blood circulation. Effleurage is used to warm up muscles and joints before a deeper massage. This helps prevent injury and makes the muscles more responsive to more intensive massage techniques. This study aimed to determine the potential of effleurage massage on the scale of back pain in third trimester pregnant women at TPMB (Midwife Independent Practice) Ratna Dewi Gunung Putri District, Bogor Regency, Indonesia. This research is an experimental research with a one group pretest-posttest design approach and uses primary data which was obtained using an assessment instrument in the form of the numeric rating scale (NRS) to determine the level of back pain in pregnant women. A total of 30 research subjects participated in this study, where the research subjects met the inclusion criteria. The research was conducted at TPMB (Midwife Independent Practice) Ratna Dewi, Gunung Putri District, Bogor Regency, Indonesia. This study shows that massage effleurage intervention is effective in reducing the intensity of back pain in pregnant women in the third trimester. There was a decrease in pain intensity after effleurage massage and it was stated to be statistically different, p<0.05. In conclusion, there is an effect of effleurage massage on back pain in third trimester pregnant women at TPMB (Midwife Independent Practice) Ratna Dewi, Gunung Putri District, Bogor Regency, Indonesia.